Exposure to the fungicide propamocarb causes gut microbiota dysbiosis and metabolic disorder in mice. (June 2018) - Wu, Sisheng; Jin, Cuiyuan; Wang, Yueyi; Fu, Zhengwei; Jin, Yuanxiang
Abstract: Propamocarb (PM) is a widely used fungicide with property of affecting fatty acid and phospholipid biosynthesis in funguses. In this study, we explored its effects on mice gut microbiota and metabolism by exposing mice to 3, 30, and 300 mg/L PM through drinking water for a duration of 28 days. We observed that the transcription of hepatic genes related to regulate lipid metabolism were perturbed by PM exposure. The microbiota in the cecal contents and feces changed during or after PM exposure at phylum or genus levels. 16S rRNA gene sequencing for the cecal content revealed shifted in overall microbial structure after PM exposure, and operational taxonomic unit (OTU) analysis indicated that 32.2% of OTUs changed by 300 mg/mL PM exposure for 28 days. In addition, based on 1 H NMR analysis, a total of 20 fecal metabolites mainly including succinate, short chain fatty acids, bile acids and trimethylamine were found to be significantly influenced by exposure to 300 mg/L PM., . These metabolites were tightly correlated to host metabolism. Our findings indicated that high doses of PM exposure could disturb mice metabolism through, or partly through, altering the gut microbiota and microbial metabolites. Graphical abstract: Image 1 Highlights: Propamocarb perturbed the transcription of hepatic genes related to lipid metabolism in mice. Propamocarb induced gut microbiota dysbiosis in mice. Propamocarb caused metabolic disorder in mice. Abstract : In this study, we were the first time to report that the fungicide of propamocarb exposure causes gut microbiota dysbiosis and metabolic disorder in mice.